Moshe Idel : representing God - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2014)
Moshe Idel, the Max Cooper Professor Emeritus at the Hebrew University of Jerusalem, and Senior Researcher at the Shalom Hartman Institute, is a world-renowned scholar of the Jewish mystical tradition. His historical and phenomenological studies of rabbinic, philosophic, kabbalistic, and Hasidic texts have transformed modern understanding of Jewish intellectual history and highlighted the close relationship between magic, mysticism, and liturgy. A recipient of two of the most prestigious awards in Israel, the Israel Prize for Jewish Thought (1999) and the Emmet Prize for Jewish Thought (2002), Idel's numerous studies have uncovered persistent patterns of Jewish religious thought that challenge conventional interpretations of Jewish monotheism, while offering a pluralistic understanding of Judaism. His explorations of the mythical, theurgical, mystical, and messianic dimensions of Judaism have been attentive to history, sociology, and anthropology, while rejecting a naïve historicist approach to Judaism.